Role of Financial Institution on the Success of Small-Scale Enterprises in Uganda: A Case Study of Lyamujungu SACCO in Kabale District. - Kyarimpa, Glorius (Kabale University, 2025)
The study investigated the Role of Financial Institutions on the Success of Small Scale Enterprises in Uganda. A case study of Lyamujungu Sacco, the objectives of the study were: to find out the role of financial training of members on the performance of Small and Medium Enterprises growth in Lyamujungu Sacco, to establish the role of financial institutions’ credit on the performance of Small and Medium Enterprises in Lyamujungu Sacco, to determine the role of unsecured loans on the performance of Small and Medium Enterprises in Lyamujungu Sacco. The study employed a descriptive study design and a cross-sectional was also used. The study used a respondent sample of 60 SMEs operating in Kabale Municipality. The study findings in respect of the main objectives indicated the role of financial training of members on the performance of Small and Medium Enterprises growth in Lyamujungu Sacco. The results also indicate that interest rates affect the borrowing of SMEs. The study results showed the role of financial training of members on the performance of Small and Medium Enterprises growth in Lyamujungu Sacco and these included; improved Financial Management, enhanced Decision-making, access to Financing, cost Control, and Efficiency, compliance and Reporting, strategic Growth. The study findings showed the role of financial institutions’ credit on the performance of Small and Medium Enterprises in Lyamujungu Sacco were survival and Resilience, improved Cash Flow Management, increased Productivity and efficiency, enhanced Market Competitiveness., employment and Economic Development, capital for Growth and Expansion. The study findings showed role of unsecured loans on the performance of Small and Medium Enterprises in Lyamujungu Sacco and these are ease of Access to Finance, supporting Cash Flow and Working Capital Needs, encouraging Entrepreneurship and Innovation, fostering Business Growth and Expansion, enhancing Financial Flexibility, reducing Financial Constraints Beck, mitigating the Impact of Credit Rationing, encouraging entrepreneurship and innovation. The study concluded by showing the role of financial institutions’ credit on the performance of Small and Medium Enterprises in Lyamujungu Sacco.